Development of tools for synergy of social functions of the state and housing mortgage loans in Russia: Regional analysis of the Central, Southern and Volga federal districts - Olga Semenyuta; Irina Dubinina; Anton Degtyarev (Journal of Risk and Financial Management, 2022)
The article researches the features of the synergy of the social functions of the state and the housing mortgage loan (HML) in order to develop a tool that allows determining guidelines and directions for strengthening the effectiveness of collaboration between the state and the private sector represented by commercial banks in solving the most important social problem-providing housing to the population. The authors show that the use of the proposed assessment tool by state structures and commercial banks increases the effectiveness of solutions to the housing problem in the country and enhances the synergetic effect of a comprehensive increase in the standard of living of the population when synchronizing actions. The main purpose of the research was to develop an algorithm that determines the key factors influencing the number of issued HML. The object of the study is the Russian HML market on the example of three federal districts. The developed algorithm is based on the use of statistical analysis methods ANOVA, mutual regression and recursive feature elimination. The approbation of the results obtained on three subjects of the Russian Federation allowed us to obtain a set of significant factors of influence, taking into account regional peculiarities.
Keywords: 330; social state; social function; housing mortgage loan; influencing factors the mortgage market; regional peculiarities Russian districts; quality of life of the people